Simulation of propranolol as antihypertensive agent on hyperglicaemic rabbit - Kus Haryono; Sukati K.; Elly Wahyuddin (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Diabetic and hypertention are two common deseases on older people one of fat soluble antihypertensive drugs is propanolol. There for is a study this undertakento observe how propanolol can reduce the blood sugar. This study used 12 male rabbits, divided into 4 grroups. Each group consisted 3 rabbits. The first group was used as negative control (given EDTA sodium liquid 1 % w/v). The second group was the treated group (given EDTA sodium suspension 1.% w/v and propranolol tablet suspension 0,006.% w/v). The third group also the treated group (given EDTA sodium suspension 1% and propranolol tablet suspension 0,02 % w/v). The fourth group was the positive control (given EDTA sodium liquid 1 % w/v only). Blood glucose level was measured before and after treatment by using spektrophotometer (578 nm). The result showed that colloidal CMC sodium liquid 1 % w/v lowered blood glucose level (not significant as 0,7 mg/dL). EDTA sodium liquid 1 % w/v + propranolol suspension 0,006 % w/v significantly lowered blood glucose level as 5,3 mg/dL, EDTA sodium liquid 1 % w/v + propranolol suspension 0,02% w/v also lowered the blood glucose level as 21,7 mg/dL, EDTA sodium liquid 1 % w/v significantly giving the effect on the increasing blood glucose level as 17,4 mg/dL.Key words : Propranolol, glucose, rabbit